Perceptions on the application of medical card towards student Part 5 ACIS UiTM Puncak Alam / Nur Farihah Mohd Fadzli. - Mohd Fadzli, Nur Farihah (2019)
Medical card is a famous product from health insurance , as we know that the establish medical card in Malaysia are high demand by the consumer especially medical card according to Syariah Compliant such as Takaful Malaysia . Takaful Malaysia was established on 29 November 1984 and after more than thirty years, this company has become one of the leading Takaful operators in Malaysia with strong financial position and risk management expertise to meet the needs of 25 service centres. This study will review on : (1) To study perceptions of understanding application of medical card (2)To study the level understanding on operation system of medical card and , (3) To identify the factor that determined to choose the medical card. This method study from collected data through google form and the respondents consist of students part 5 Acis Uitm Puncak Alam to achieve the objective. Based on the data from respondents , majority respondents know the medical card are important but there are a lot of people did not consumption the medical card maybe the students did not money to spend money on medical card. So the authorities should ensure to do the recommendations a few elements : (1) Do the exposure the application medical card (2) Improve the facilities of medical card